Assessing the Subchronic Toxicity of the Ethanolic Extract of the Pods of Tetrapleura tetraptera on Swiss Albino Mice - Oloyede Michael Adeola * (Lorestan University of Medical Sciences, 2018)
Background and Aim: Tetrapleura tetraptera fruit is widely used in south-east and western Nigeria not only as a spice but also as a remedy for various ailments. This research aims at examining the subchronic toxicity of the ethanolic extract of the pods of T. tetraptera on Swiss albino mice. Materials and Methods: Twenty-five Swiss albino Wistar mice weighing between 18-30g were randomly divided into five groups. Animals in group 1 that was regarded as the control group were administered distilled water. Animals in group 2-4 were orally administered 50,100 and 200mg kg-1 bodyweight of T. tetraptera. All animals were fasting on the eve of the 43rd day. Following the withdrawal of treatment, the blood, liver, kidneys, lungs and heart were removed for hematologic, biochemical and histologic investigations. Results: No remarkable alteration was observed in the hematologic parameters except for the significant reduction in the WBC. The biochemical investigation indicated gross changes in most of the biochemical analytes dose-dependently. The levels of ALT, ALP, TB, DB, PRO, CREA, UREA, ALB and CHOL were all noticeably (P˂0.05) different from the control group in all doses which might be indicative of toxicity. Moreover, some minor changes were observed in the histoarchitecture of the liver and the kidney. Conclusion: Hence, the results revealed that the extract might have induced toxicity to the kidneys and liver which may in turn influence other parts of the body. Tetrapleura tetraptera may contain some phytochemicals, which on prolonged use may affect the physiology of the body.